Infusing Ubuntu as a principle towards improving social development : a social work perspective - Mabasa, M. A. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
The South African government has adopted services standards access, courtesy, information, openness and transparency, redress and value for money as principles of accelerating service delivery. Yet "Ubuntu" is an African philosophy that is internalised amongst the African people to beef up optimal social interaction, development and the welfare of the society. Infusing "Ubuntu" as a basic principle to enhance social service delivery is of paramount importance and in the interest of social development for the South African people. The study sought to describe the infusion of "Ubuntu" as a principle towards the improvement of social development amongst social work professionals in gearing the Integrated Social Service Delivery Model in the social services sector. The qualitative approach, descriptive design, convenient sampling, semi-structured interview schedule and thematic analysis were used to systematically assess the study about infusing "Ubuntu" as a principle towards improving social development amongst social workers. The study revealed that to incorporate "Ubuntu" as a principle towards gearing service delivery is in the interest of the society as it enables people in different spaces to work collectively. Furthermore, the study revealed that infusing "Ubuntu" allows people in different positions to see themselves as equal human beings in order to set social solidarity and justice. The study concluded that infusing "Ubuntu" strengthens the delivery of services to the communities by social workers with other stakeholders as part of the social development landscape. It was recommended that the South African government should infuse "Ubuntu" as a major principle towards gearing social development.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Infusing; Social development; Social work perspective; Ubuntu; Ubuntu; Public welfare